PEMANFAATAN SABUT KELAPA DAN SEBAGAI MEDIA TANAM DALAM KAWASAN PANGAN LESTARI - Badrul ainy dalimunthe, Rosmidah hasibuan, Syahrizal efendi lubis, Aulia ramadani br rambe, Bhinekta (PT.JNDI, JURNAL BIMA, 2025)
Sustainable Food Areas (KPL) are strategic programs to increase community food self-sufficiency through the utilization of yard land and appropriate technology. One innovation that can be implemented is the use of organic and inorganic waste as alternative planting media. This article discusses the use of coconut fiber as organic waste and jute as inorganic waste, which are recycled into planting media in KPL. This method not only helps provide healthy food for the community but also contributes to reducing household waste generation. The results of the study indicate that coconut fiber has high water absorption and is able to maintain soil moisture, while jute can be used as an environmentally friendly planting medium.